A new species of Lepanthes (Orchidaceae: Pleurothallidinae) with rabbit ear-like petals endemic to Colombia - Restrepo, Eugenio (2022)
A new species of Lepanthes from the department of Antioquia apparently restricted to the north-central Andes of Colombia is described and illustrated. The new species is similar to L. alcicornis; however, it can be easily distinguished by the transversally lobulate petals that resemble the ears of a rabbit, the reniform lip with sub-oblong basal lobes surrounding the column, and the absence of an appendix on the lip.